COMMERCIAL DISPUTE RESOLUTION: STRATEGIES FOR RESOLVING INTERNATIONAL COMMERCIAL DISPUTES THROUGH ARBITRATION AND MEDIATION - Stradella, Rafaella (LUMEN ET VIRTUS, 2023)
The increasing globalization of commerce has led to a corresponding rise in international commercial disputes, necessitating efficient and effective methods for cross-border conflict resolution. Traditional litigation often fails to meet the demands of international commerce due to jurisdictional challenges, high costs, and procedural delays. Consequently, arbitration and mediation have emerged as vital alternatives, offering greater procedural flexibility, neutrality, and enforceability—particularly through international frameworks such as the New York Convention (1958) and the Singapore Convention (2019). Arbitration is recognized for its binding nature and global enforceability, while mediation is valued for its collaborative approach and cultural adaptability. Hybrid mechanisms, such as med-arb and arb-med-arb, further enhance the dispute resolution process by combining the strengths of both methods. This article analyzes these alternative dispute resolution strategies and highlights the importance of well-drafted dispute resolution clauses to maximize their effectiveness in international contracts.